The P2X7 Receptor Is Shed Into Circulation: Correlation With C-Reactive Protein Levels - Giuliani, Anna Lisa; Berchan, Merhej; Sanz, Juana M.; Passaro, Angelina; Pizzicotti, Stefano; Vultaggio-Poma, Valentina; Sarti, Alba Clara; Di Virgilio, Francesco (Frontiers in Immunology, 2019)
The P2X7 receptor (P2X7R) is a key pro-inflammatory plasma membrane receptor responsible for NLRP3 inflammasome activation and IL-1β release. Various inflammatory plasma membrane receptors (e.g. IL-1 type I receptor, TNF type I and II receptors, IL-2 receptor) are shed under different pathophysiological conditions. In the present study, we show that the full length P2X7R is released into circulation in patients as well as in healthy subjects. Blood levels of shed P2X7R (sP2X7R) correlate to those of the inflammatory marker C reactive protein (CRP). Blood sP2X7R ranged from 16.74 to 82.17 ng/L, mean ± SE 40.97 ± 3.82 (n = 26) in healthy subjects, from 33.1 to 484.0 ng/L, mean ± SE 114.78 ± 12.22 (n = 45) in patients with CRP < 3 mg/L, and from 63.65 to 1092.3 ng/L, mean ± SE 204.2 ± 30.94 (n = 42) in patients with CRP > 3 mg/L. sP2X7R in plasma was largely associated to microvesicles/microparticles. Peripheral blood monocytes from healthy subjects released sP2X7R upon stimulation with the semi-selective P2X7R agonist benzoyl ATP. These data show that the P2X7R can be released into circulation, and that its blood levels increase in various disease conditions.